Institutionalizing quality within national health systems: key ingredients for success. (8th December 2019) - Kandasami, Stephanie; Syed, Shamsuzzoha Babar; Edward, Anbrasi; Sodzi-Tettey, Sodzi; Garcia-Elorrio, Ezequiel; Mensah Abrampah, Nana; Hansen, Peter M
Abstract: Quality improvement initiatives can be fragmented and short-term, leading to missed opportunities to improve quality in a systemic and sustainable manner. An overarching national policy or strategy on quality, informed by frontline implementation, can provide direction for quality initiatives across all levels of the health system. This can strengthen service delivery along with strong leadership, resources, and infrastructure as essential building blocks for the health system. This article draws on the proceedings of an ISQua conference exploring factors for institutionalizing quality of care within national systems. Active learning, inclusive of peer-to-peer learning and exchange, mentoring and coaching, emerged as a critical success factor to creating a culture of quality. When coupled by reinforcing elements like strong partnerships and coordination across multiple levels, engagement at all health system levels and strong political commitment, this culture can be cascaded to all levels requiring policy, leadership, and the capabilities for delivering quality healthcare.